Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran IPAS Menggunakan Model Cooperative Learning Tipe Teams Games Tournament (TGT) di Kelas V SDN 9 Sijunjung - Mifta Hurrahmi; Sartono Sartono; Arwin Arwin; Syofianti Engreini (Pusat Riset dan Inovasi Nasional, 2025)
This research is prompted by the low achievement of student learning outcomes in IPAS learning, which is caused by the less than optimal implementation of the learning model carried out by the teacher. So that students are less active in participating in learning, which has an impact on the low learning outcomes of students. The purpose of this study was to describe the improvement of student learning outcomes in IPAS learning using the Teams Games Tournament (TGT) type Cooperative Learning model in class V SDN 9 Sijunjung. This research is a Classroom Action Research (PTK) using a qualitative research design conducted at SDN 9 Sijunjung with the subject being grade V students at SDN 9 Sijunjung consisting of 14 male students and 13 female students This research was conducted in two cycles, namely cycle I two meetings and cycle II one meeting. The research process involved four main stages: planning, action, observation and reflection. The results showed an increase from cycle I to cycle II, the average value of the learning module increased from 87.49 (B) in cycle I to 95.83 (A) in cycle II. Teacher activity also increased from an average score of 87.49 (B) cycle I to 96.42 (A) cycle II. Learner activities also increased from 87.49 (B) cycle I to 96.42 (A) cycle II. The learning outcomes of students also showed a significant increase from 75 (C) in cycle I to 91 (A) in cycle II.Overall, the Cooperative Learning model type Teams Games Tournament (TGT) has been proven to be able to improve the learning outcomes of students in class V at SDN 9 Sijunjung